Answer:
![P(x) = x - x^2 + x^3 - x^4+x^5](https://img.qammunity.org/2020/formulas/mathematics/college/6uehgef7y8m9qzuxwdan1mso6ezpfz0wc1.png)
Explanation:
Let us first remember how a Taylor polynomial looks like:
Given a differentiable function
then we can find its Taylor series to the
degree as follows:
![P(x) = f(x_(0)) + f'(x_(0)).(x-x_(0)) + (f''(x_(0)))/(2!).(x-x_(0))^2+.....+(f^n(x_(0)))/(n!).(x-x_(0))^n + R_(n)(x).(x-x_(0))^n](https://img.qammunity.org/2020/formulas/mathematics/college/6oa3er3h1ww8ay9fgb4p3dn9ce01isargw.png)
Where
represents the Remainder and
is the
derivative of
.
So let us find those derivatives.
![f(x) = (x)/(1+x)\\f'(x) = (1)/((1+x)^2)\\f''(x) = (-2)/((1+x)^3)\\f'''(x) = (6)/((1+x)^4)\\f''''(x) = (-24)/((1+x)^5)\\f'''''(x) = (120)/((1+x)^6)](https://img.qammunity.org/2020/formulas/mathematics/college/95m9nh7pxk53nnu9w6q5oogiyst02usx5g.png)
The only trick for this derivatives is for the very first one:
![f'(x) = (1)/(1+x) - (x)/((1+x)^2)\\f'(x) = ((1+x) - x)/((1+x)^2) = (1)/((1+x)^2)\\](https://img.qammunity.org/2020/formulas/mathematics/college/rs7rrj94ibrr5l0as0dc66rnwdrdiaec6o.png)
Then it's only matter of replacing on the Taylor Series and replacing
![x_(0)=0](https://img.qammunity.org/2020/formulas/mathematics/college/ohumgu2huu5ra4kkzu9up812npoywmt8c7.png)